Review of the Validity and Legal Justice of the Prosecutor's Demands in the Corruption Case Number: 2/Pid.Sus.TPK/2023/PN.Mks - Khaidir, Khaidir; Shodiq, MD; Prasetyo, Dedy Ardian (MAQASIDI: Jurnal Syariah dan Hukum published by the Islamic Criminal Law Program of the Sharia and Islamic Economics Department at the Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh, 2024)
The validity and fairness of the law against the charges are very important to be considered by the Public Prosecutor. The prosecution process by the public prosecutor begins with the study of the investigation file, then from the results of the public prosecutor's research can identify what evidence and the evidentiary strength is fulfilled, then for the inherent weaknesses known in the case file to prepare the juridical—accurate facts to anticipate problems that arise in the effort to prove in court. The problem in this paper is the basis for the Public Prosecutor's consideration regarding the Corruption Crime case and how to review the aspects of legality and legal justice against the Public Prosecutor's demands in case Number: 2/Pid.Sus.TPK/2023/PN.Mks. This paper uses a type of normative juridical method with the consideration that the problem being studied is relevant to the regulations and how to handle it in judicial practice. From the results of the research carried out, it can be concluded as follows: first, the Public Prosecutor in his Indictment in the form of an